Beyond `crude pragmatism` in sports coaching: Insights from C.S. Peirce, William James and John Dewey: A Commentary - Turner, D. (International Journal of Sports Science & Coaching, 2017)
The latest incarnation of my Learning From Legendary Coaches project, is based upon a hundred year plus direct lineage of interrelated coaching influences in football, featuring Jack Reynolds, Rinus Michels, Johan Cruyff, and Pep Guardiola. In resonance with the Peircian spirit, these coaches successively came to love what they did, inspired others through their coaching, used their own accumulated histories, and grasped opportunities to learn further through experimentation, and in so doing affected the evolution of football, and the evolution of themselves. Their stories feature risk, revision and reinvigoration, built in part on inherited foundations from an intergenerational community of inquiry (Peirce emphasised the importance of community in the development of the individual), in constantly striving for improvement and seeking a sense of a rightness of direction. This project, and my aforementioned research into the long-term developmental journeys towards expertise of performance coaches, might be taken to represent attempts at the empirical philosophical enquiry that Cushion and Partington called for (albeit that the former relies upon secondary rather than primary data), given that they investigate the formative influences upon, the development and redevelopment of, and the expression and consequences in action of, coach`s evolving philosophies over extended periods of time. FROM AUTHOR